2017
DOI: 10.1515/picbe-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Review on the dimensions of business-university alliances

Abstract: The present paper is concerned with identifying and synthesizing the directions of development of the partnerships between the academic environment and the business environment found in main research dedicated articles in the last five years in three relevant databases: Thomson Reuters Web of Knowledge, Science Direct and PROQUEST Central. The method we employed consists in tertiary data selection, processing and filtering by means of adequate software. The thorough literature review on partnerships between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
(14 reference statements)
1
15
0
Order By: Relevance
“…Companies in the Middle East region are not fully aware of significances of environmental protection policies, and thus, unintentionally risk the environment by further exploration and production activities. Given the fact that almost half of the respondents to this survey indicated that there is no specific department responsible for sustainability in their organization, a comprehensive approach must be taken to educate managers and employees to improve the quality of services to the industry and relevant customers now, and in coming future (Dima et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Companies in the Middle East region are not fully aware of significances of environmental protection policies, and thus, unintentionally risk the environment by further exploration and production activities. Given the fact that almost half of the respondents to this survey indicated that there is no specific department responsible for sustainability in their organization, a comprehensive approach must be taken to educate managers and employees to improve the quality of services to the industry and relevant customers now, and in coming future (Dima et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the internationalization process finds itself in a dynamic rhythm [27] and adds more pressure towards implementing practically the efforts for a sustainable economic development and restructuring of the business field in order to reduce waste generation. Practices, such as corporate social responsibility measures directed towards environmental friendly actions, as well as clearer legislations, clusters for cooperation of several institutions [28] and partnerships between the academic field and the business environment [29] are considered to be contributing to the efforts in the sense of a sustainable approach for the environment protection in the sense of diminishing waste from the beginning of the production process, as well as after consumption of the product. In order to reduce generation of waste or emissions, new approaches and methods are starting to be implemented in the business field, such as in the case of reducing or treatment of municipal waste or reducing the CO 2 emissions from the iron and steel processes [30].…”
Section: Literaturementioning
confidence: 99%
“…Any person concerned has the right to obtain from the operator, on request and free of charge with a request per year, the confirmation that the data concerning him / her are processed or not by him / her. For example, the commercialization of property rights between universities and companies (Dima, et al, 2017). An operator is obliged, when processing personal data concerning the applicant, to communicate to him, together with the confirmation, at least the following: information on the purposes of the processing, the categories of data concerned and the recipients or categories of recipients to whom the data are disclosed; communicating in an intelligible form the data subject to processing, as well as any available information on the origin of the data; information on the operating principles of the mechanism by which any automatic processing of data relating to that person is carried out; information on the existence of the right to interfere with data and the right to object and the conditions under which they may be exercised.…”
Section: Personal Datamentioning
confidence: 99%